Taurocholate Deconjugation and Cholesterol Binding by Indigenous Dadih Lactic Acid Bacteria - USMAN PATO; MUHAMMAD ALI; ABDUL K. PARLINDUNGAN (HAYATI Journal of Biosciences, 2005)
High serum cholesterol levels have been associated with an increased risk for human coronary heart disease. Lowering of serum cholesterol has been suggested to prevent the heart disease. To reduce serum cholesterol levels one may consumed diet supplementat of fermented dairy product such as dadih. Lactic acid bacteria present in dadih may alter serum cholesterol by directly bind to dietary cholesterol and/or deconjugation of bile salts. Acid and bile tolerance, deconjugation of sodium taurocholate, and the cholesterol-binding ability of lactic acid bacteria from dadih were examined. Among ten dadih lactic acid bacteria tested, six strains namely I-11, I-2775, K-5, I-6257, IS-7257, and B-4 could bind cholesterol and deconjugate sodium taurocholate. However, the last four strains were very sensitive to bile. Therefore, Lactobacillus fermentum I-11 and Leuconostoc lactis subsp. lactis I-2775 those were tolerant to acid and oxgall (bile) and deconjugated sodium taurocholate and bound cholesterol could be recommended as probiotic to prevent coronary heart disease.